The Great Jedi Rescue - Scott, Cavan; Pur Antonsson, 1984- (Los Angeles, California : Disney/Lucasfilm Press, 2021)
"When a disaster in hyperspace puts the people of Hetzal Prime in danger, only the brave Jedi--the guardians of peace and justice--can save the day." -- Page [4] cover.
Keywords: Jedi (Fictitious characters) -- Juvenile fiction; Interplanetary voyages -- Juvenile fiction; Life on other planets -- Juvenile fiction; Fiction; Juvenile works; Picture books; Science fiction